2019
DOI: 10.5005/jp-journals-10005-1652
|View full text |Cite
|
Sign up to set email alerts
|

Caries Experience and Oral Health-related Factors of Kuwaiti Preschool Children and their Mothers: A Pilot Study

Abstract: AimThe objective of this study was to investigate the association between the caries experience and oral-health-related behavior of Kuwaiti preschool children and their mothers.Materials and methodsA convenience sample of 84 participants (42 child–mother pairs) was selected. Data regarding children's and mothers’ demographics, oral hygiene practices, and dietary habits were obtained by questionnaires. Oral clinical examinations were carried out on the participant children and mothers to determine their caries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…On analyzing maternal influencing factors in the development of caries in their children, the multivariate analysis could only confirm an association with the condition of being an immigrant mother, (OR = 12.661). Association with other factors described in previous studies, such as the age of the mother [ 49 ], smoking habits [ 50 ], the activity of caries [ 51 ], or the consumption of sweets or snacks [ 50 ], were not confirmed.…”
Section: Discussionmentioning
confidence: 70%
“…On analyzing maternal influencing factors in the development of caries in their children, the multivariate analysis could only confirm an association with the condition of being an immigrant mother, (OR = 12.661). Association with other factors described in previous studies, such as the age of the mother [ 49 ], smoking habits [ 50 ], the activity of caries [ 51 ], or the consumption of sweets or snacks [ 50 ], were not confirmed.…”
Section: Discussionmentioning
confidence: 70%
“…32 Anyhow, most mothers' oral health behaviors did not show correlations with the dental status of their children in our study; similar to Husain et al study, where no relationship between the oral health behaviors of the mothers and their children was found. 44 In respect to children' oral health behaviors, the frequency of brushing teeth of children was correlated with their oral health status in the current study. It might be attributed to the fact that children' ability to clean their teeth where no correlation between children oral health behaviors and their dental caries experience, 44 but was consistent with the findings of others.…”
Section: The Effect Of Oral Health Behaviors Of Mothers and Their Chi...mentioning
confidence: 74%
“…44 In respect to children' oral health behaviors, the frequency of brushing teeth of children was correlated with their oral health status in the current study. It might be attributed to the fact that children' ability to clean their teeth where no correlation between children oral health behaviors and their dental caries experience, 44 but was consistent with the findings of others. 45,46 Improving children' oral health behaviors is an important target, because children who are introduced to good health habits in early childhood, this good behavioral approach tends to continue later into adulthood.…”
Section: The Effect Of Oral Health Behaviors Of Mothers and Their Chi...mentioning
confidence: 74%
See 1 more Smart Citation
“…Dye and colleagues found that the children of mothers with untreated dental caries were three times as likely to have untreated dental caries themselves [25]. Several other investigations carried out in diverse settings relied on clinical or guardian-reported data and consistently and positively associated parents' oral health with that of their children's [26][27][28][29]. From a practical, clinical, and public health standpoint, modifiable oral health behaviors (e.g., diet and oral hygiene) [30], guardians' oral health literacy [15], and dental neglect [31] are logical targets for interventions seeking to break the intergenerational cycle of poor oral health.…”
Section: Discussionmentioning
confidence: 99%